Pengaruh Kualitas Layanan Terhadap Tingkat Kepuasan Masyarakat Pada Kantor Imigrasi Bengkalis - Muhammad Fadhil Junery; Nur Asyira (LPPM ISNJ Bengkalis, 2020)
This research aims to determine the immigration office services providing services to the community and how much influence the quality of immigration office services on the level of community satisfaction. This research uses a descriptive quantitative method. The population in this research amounted to 21613 people. While sampling uses the Slovin formula with convenience sampling technique so that a sample of 100 people is obtained. Data collection techniques used were observation, interviews, documentation, questionnaires and literature studies. The results of this research are that the service at the Bengkalis Immigration Office has been well fulfilled based on the determination of the central government. Then the service quality of Bengkalis Immigration Office has a significant effect on the level of community satisfaction with a percentage of influence of 68.6% and the remaining 31.4% is influenced by other variables.